Implementation of RFID technology for the differentiation of loyalty programs - (:unkn) unknown (ISTANBUL TECHNICAL UNIV, 2007)
Customer orientation has been seen as a magic formula since 1980. Many companies invested a lot of money to change their IT systems in order to be more customer oriented, thus many different industries (retail, banking, airlines, insurance, hotels etc.) began with different CRM programs. Today nearly every company offers a different CRM or loyalty program. In the year of 2007, the problem is differentiation of Loyalty Programs. As a marketing and customer manager, you have to be more accurate, more knowledgeable and faster than your competitors in terms of serving your best customer. In order to achieve this, you will to obtain important information from your customer without bothering him/her. Each time the customer will visit your company, you have to learn about him/her, about his/her needs, wishes and in return you have to optimize your offer according to her/his preferences. For building this kind of a learning relationship, companies have to use the latest technology. The aim of our study is to show this cooperation between CRM and latest technology of RFID. RFID has been used in many different industries and mainly for logistics reasons. But we believe that it could serve as a CRM tool as well. We have implemented a model for retail sector and explained the win-win strategies for customers, suppliers and for the store management.
Keywords: TRENDS